Classificação morfológica na escala de detalhe no Pontal do Paranapanema, SP - Cardoso, Anna Carolina dos Santos; Nepomuceno, Pablo Luíz Maia (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2020)
The present article aims to present the feasibility of the morphological classification in a scale of relief detail in hydrographic basins, according to the legends proposed by Colangelo (1996), corresponding to the Elementary Units of Relief; and the fifth taxon of the  taxonomy proposed by Ross (1992), referring to the types and forms of slopes using geoprocessing techniques. To this end, two hydrographic sub-basins of the Santo Anastácio River, located in the Pontal do Paranapanema region, were taken as a case study. The morphological compartments were classified through the processing of Digital Elevation Models - DEM and orthophoto in a Geographic Information Systems (GIS) environment. These data were made available by Emplasa (2011), and come from the “Mapeia São Paulo” project, the last systematic survey of topographic and aerophotogrammetric data carried out for the entire state of São Paulo. As a result, nine possible classes of Elementary Relief Units and, at least, six different classes of types and forms of slopes were obtained, thus confirming the technical and methodological feasibility of the procedures adopted about the treatment of the data used to carry out the classification. morphological in the detail scale in hydrographic basins of the Pontal do Paranapanema region.